Parental financial socialisation of young black African adults in South Africa - Adam Ndou (Global Business & Finance Review (GBFR), 2024)
Purpose: Parental financial socialisation is necessary to help young adults to effectively manage their finances and improve their financial well-being. This study examined parental financial socialisation of young black African adults by their parents in rural and low-income area in South Africa. Design/methodology/approach: Parental financial socialisation was measured through parental financial behaviour, parental financial monitoring, parental financial discussions, parental financial communications, and parental finan-cial teaching. This study adopted quantitative research approach and self-administered questionnaire to collect data from young black African adults in Fetakgomo Tubatse and Intsika Yethu municipalities because these municipal-ities are the most rural and low-income areas in South Africa. Descriptive statistics were used to analyse data. The composite score was calculated to determine parental financial socialisation. Findings: The overall score of Parental financial socialisation was 53%, which is moderate. Thus, young black African adults are financially socialised by their parents. This result was surprising as parents in rural and low-income areas uphold cultural norms and values and consider discussing certain issues like money with children a taboo. Research limitations/implications: Due to the low levels of general literacy among the respondents, which neg-atively affected data collection; some young adults did not understand the questionnaire and withdrew from partic-ipating in the study. Furthermore, even though confidentiality and anonymity were guaranteed, respondents were reluctant to participate in the study. They feared exposing their financial position and displayed a lack of trust. Originality/value: This study is the first to investigate parental financial socialisation of young black African adults in rural and low-income area in South Africa. This study concluded by providing recommendations and suggestions for future research.
Keywords: 650; Parents; Financial socialisation; Young adults; South Africa